2018
DOI: 10.1111/lam.12833
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous anti-diabetic and anti-vascular calcification activity of Nocardia sp. UTMC 751

Abstract: Actinobacteria are one of the best natural libraries for discovering drugs. Various commercial drugs have been developed against infectious and metabolic disorders from actinobacteria; however, there is no report on their simultaneous inhibitory effect against diabetes, a life-threatening disease, and its related pathological processes, like inflammation and vascular calcification (VC). In this research, after several screening, Nocardia sp. UTMC 751 was introduced as the first microbial source exhibiting a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…However, a few studies found that some of these natural compounds also have a protecting effect against vascular calcification. Recent studies have demonstrated that the extract of actinomycetes fermentation broth may provide a novel treatment for vascular calcification by inhibiting the expression of osteogenic genes, the VSMC oxidative stress and apoptosis rate 31,32 . In this study, we chose the CEL as a candidate natural compound considering clinically its long‐term use in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a few studies found that some of these natural compounds also have a protecting effect against vascular calcification. Recent studies have demonstrated that the extract of actinomycetes fermentation broth may provide a novel treatment for vascular calcification by inhibiting the expression of osteogenic genes, the VSMC oxidative stress and apoptosis rate 31,32 . In this study, we chose the CEL as a candidate natural compound considering clinically its long‐term use in China.…”
Section: Discussionmentioning
confidence: 99%
“…**P < .01 and ***P < .001 indicate significant differences between the indicated columns have demonstrated that the extract of actinomycetes fermentation broth may provide a novel treatment for vascular calcification by inhibiting the expression of osteogenic genes, the VSMC oxidative stress and apoptosis rate. 31,32 In this study, we chose the CEL as a candidate natural compound considering clinically its longterm use in China. Root extracts from TGV are routinely used in the treatment of rheumatoid arthritis and are found to be highly effective.…”
Section: Cel Down-regulated the Expression Of Bmprii And Up-regulatmentioning
confidence: 99%
“…Microorganisms are the more readily reproducible source of bioactive compounds in comparison to the plants and animals. According to the statics of the microbial-derived commercial drugs, actinomycetes, fungi, and myxobacteria are the richest bioresources of structurally unique and medically important compounds (Harvey, 2008;Reichenbach, Gerth, Irschik, Kunze, & Höfle, 1988;Fatemeh Salimi, Hamedi, Motevaseli, & Mohammadipanah, 2019;F Salimi, Jafari-Nodooshan, Zohourian, Kolivand, & Hamedi, 2018;Schaberle, Lohr, Schmitz, & Konig, 2014;Vasundhara, Reddy, & Kumar, 2019;Watve, Tickoo, Jog, & Bhole, 2001). Many compounds with anti-inflammatory activity have been extracted from microorganisms and an overview of these prodrugs is summarized in Tables 1 and 2.…”
Section: Microbial Derived Anti-inflammatory Compoundsmentioning
confidence: 99%
“…We identified five types of potential antioxidants with therapeutic effects against VC based on the literature search, including linalool 61 , lipoic acid 2224 , rosmarinic acid 63 , fermentation broth extracts from Actinobacteria 59 , and polysaccharide from Fuzi product 60 . Two (40%) of them have ROS scavenging ability, while the other three (60%) do not (Fig.…”
Section: Antioxidants From Natural Non-dietary Sourcesmentioning
confidence: 99%
“…Preliminary results from Liao et al showed that polysaccharide extracted from Radix Aconiti Carmichaeli , a raw product with anti-oxidant activity, could reduce calcification severity of ox-LDL-treated VSMCs, partially by activating autophagy 60 . Salimi et al also found that metabolites extracted from cultured Nocardia strain could attenuate protein oxidation, reduce inflammation, and reduce VSMC calcification severity 59 . The potential downstream effectors of these natural non-dietary compounds are summarized in Fig.…”
Section: Antioxidants From Natural Non-dietary Sourcesmentioning
confidence: 99%